Homeless people: what are my rights? A community experience through photography - Nina, Ruth; Ostolaza, Cesar; Rodríguez, Francisco (Revista de Psicología, 2013)
The current work describes a community experience that emerged from the need to study the homeless population through other methodologies. A workshop was designed using the Ander-Egg (2000) methodology "Learning by doing something", in conjunction with photography as a mean of expression. This was implemented to reflect on homeless rights in the human rights context. Each workshop dealt specifically with the right for housing, health, food and work, and reflected on each particular daily life situation. In the workshops seven homeless individuals (one woman and six men) participated, with an average 51 years of age, and with incomplete high school education. At the moment, they were homeless for more than a year and all of them were residents of the city of Río Piedras. The participants were trained on how to use a camera, with the purpose of documenting social coexistence and human rights. A total of five workshops were scheduled and delivered to participants, one for each theme. The participants had to use the camera capturing photographs of the theme worked on. Each participant photographed an average of 16 photos, obtaining a total of 114 photos. The images were presented by the creators themselves and presented in a public activity. It was concluded that this population has a critical view of the realities they live, recognizing various obstacles they face in their daily lives.